Β-blockers, calcium antagonists, and mortality in stable coronary artery disease: an international cohort study. (7th May 2019) - Sorbets, Emmanuel; Steg, Philippe Gabriel; Young, Robin; Danchin, Nicolas; Greenlaw, Nicola; Ford, Ian; Tendera, Michal; Ferrari, Roberto; Merkely, Bela; Parkhomenko, Alexander; Reid, Christopher; Tardif, Jean-Claude; et al.
Abstract: Aims: The effect of first-line antianginal agents, β-blockers, and calcium antagonists on clinical outcomes in stable coronary artery disease (CAD) remains uncertain. Methods and results: We analysed the use of β-blockers or calcium antagonists (baseline and annually) and outcomes in 22 006 stable CAD patients (enrolled 2009–2010) followed annually to 5 years, in the CLARIFY registry (45 countries). Primary outcome was all-cause death. Secondary outcomes were cardiovascular death and the composite of cardiovascular death/non-fatal myocardial infarction (MI). After multivariable adjustment, baseline β-blocker use was not associated with lower all-cause death [1345 (7.8%) in users vs. 407 (8.4%) in non-users; hazard ratio (HR) 0.94, 95% confidence interval (CI) 0.84–1.06; P  =   0.30]; cardiovascular death [861 (5.0%) vs. 262 (5.4%); HR 0.91, 95% CI 0.79–1.05; P  =   0.20]; or cardiovascular death/non-fatal MI [1272 (7.4%) vs. 340 (7.0%); HR 1.03, 95% CI 0.91–1.16; P  =   0.66]. Sensitivity analyses according to β-blocker use over time and to prescribed dose produced similar results. Among prior MI patients, for those enrolled in the year following MI, baseline β-blocker use was associated with lower all-cause death [205 (7.0%) vs. 59 (10.3%); HR 0.68, 95% CI 0.50–0.91; P  =   0.01]; cardiovascular death [132 (4.5%) vs. 49 (8.5%); HR 0.52, 95% CI 0.37–0.73; P  =   0.0001]; and cardiovascular death/non-fatal MI [212 (7.2%) vs. 59 (10.3%); HR 0.69, 95% CI 0.52–0.93; P  =   0.01]. Calcium antagonists were not associated with any difference in mortality. Conclusion: In this contemporary cohort of stable CAD, β-blocker use was associated with lower 5-year mortality only in patients enrolled in the year following MI. Use of calcium antagonists was not associated with superior mortality, regardless of history of MI.